Analysis on gender equality in Norharyati Kaprawi’s works - Indriaty Ismail; Nuramalina Huda Yahya; Faiz Hadi Sanadi (Penerbit Universiti Kebangsaan Malaysia, 2020)
The term gender equality refers to equality between men and women. It is the only term aimed at campaigning against men's injustice and violence against women, and vice versa. Generally, the public recognizes that gender equality is a story of male violence against women. The violence is aimed at harming women physically, sexually or psychologically, and such violent acts affect women physically, sexually or psychological because they are the victim. Sisters in Islam is a civil society organization promoting the rights of women within the frameworks of Islam and universal human rights in Malaysia. Norhayati Kaprawi is one of the very active and productive activists of this civil society organization; she has produced the videos films and documentaries containing her views on women's issues in Malaysia. This article aims at identifying and analyzing Norhayati’s ideas and views on gender equality and feminism, the resources or references as well as the methodologies stating explicitly or implicitly in her works. The methodology of content analysis approach is used in this article to analyze the contents of her videos such as Female Ulama: Fatimah Al-Samarqandi, Female Ulama: Sayyidah Nafisah Binti Hassan: Guru Imam Syafie and Sejarah Rosie the Riveter. In identifying and analyzing her views and ideas in her videos, this article also refers to some relevant written materials and documents such as the books, the news porters and the newspapers. This article discovers that her methodology is historical, and her views on gender equality between men and women are inclined to the Western understanding.